Plan C : community survival strategies for peak oil and climate change - Murphy, Eugene (Eugene R.) (New Society Publishers, 2008)
Concerns over climate change and energy depletion are increasing exponentially. Mainstream solutions still assume a panacea that will cure our climate ills without requiring any serious modification to our way of life. Plan C explores the risks inherent in trying to continue our energy-intensive lifestyle. Using dirtier fossil fuels (Plan A) or switching to renewable energy sources (Plan B) allows people to remain complacent in the face of potential global catastrophe. Dramatic lifestyle change is the only way to begin to create a sustainable, equitable world. The converging crises of Peak Oil.